Flexible and ultrathin waterproof conductive cellular membranes based on conformally gold-coated PVDF nanofibers and their potential as gas diffusion electrode. (January 2023) - Yu, Ranxue; Senocrate, Alessandro; Bernasconi, Francesco; Künniger, Tina; Müller, Luca; Pauer, Robin; Battaglia, Corsin; Wang, Xinhou; Wang, Jing
Graphical abstract: Highlights: Three-dimensional and conformal gold-coated PVDF nanofibers are successfully fabricated by electrospinning and electroless plating. Excellent conductivity, hydrophobicity, and good mechanical flexibility are obtained by microstructural control and gold coating. Gold-coated PVDF membranes demonstrate the suitability for electrochemical CO2 reduction and achieve high current density of 100 mA/cm 2 . Abstract: Nanofiber membranes (NFMs) coated with noble metals are intensively researched for various applications such as wearable electronics, environmental sensors, and point of care diagnostics. To achieve the desired functionality while minimizing costs, a combination of facile coating methods and accurate microstructural designs is required, but remains elusive. Herein, novel conductive and porous membranes are designed based on a facile and scalable approach to fabricating conformally coated gold layers on electrospun PVDF fibers (Au-PVDF-NFMs) via electroless plating. The deposition of a conformal and fully interconnected gold layer with an average thickness of circa 38 nm on the surface of nanofibers is confirmed by systematic characterizations. The high-conjunction gold layers endows a high electrical conductivity to the membranes, yielding a low sheet resistance of 1.2 Ω/sq. In addition, the membranes show integrated functionalities such as hydrophobicity and gas permeability. Notably, the NFMs also show excellent mechanical durability under both stretching and bending, with negligible conductivity losses after 1000 test cycles. Thanks to these properties, the Au-PVDF-NFMs demonstrates practical suitability as gas diffusion electrodes (GDEs) for electrochemical CO2 reduction. The Au-PVDF-NFMs exhibit a substantial Faradaic efficiency towards CO, as high as ∼ 85 % at −0.7 V vs reversible hydrogen electrode (RHE), and are able to reach current densities of 100 mA cm −2 at −0.95 V versus RHE.